Significant spread of extensively drug‐resistantAcinetobacter baumanniigenotypes of clonal complex 92 among intensive care unit patients in a university hospital in southern Iran. Issue 11 (November 2017) - Saffari, Fereshteh; Monsen, Tor; Karmostaji, Afsaneh; Azimabad, Fahimeh Bahadori; Widerström, Micael
Abstract : Purpose. : Infections associated with Acinetobacter baumannii represent an increasing threat in healthcare settings. Therefore, we investigated the epidemiological relationship between clinical isolates of A. baumannii obtained from patients in a university hospital in Bandar Abbas in southern Iran. Methodology. : Sixty‐four consecutive non‐duplicate clinical isolates collected during 2014‐2015 were subjected to susceptibility testing, clonal relationship analysis using PFGE, multilocus variable‐number tandem‐repeat analysis (MLVA) and multilocus sequence typing (MLST), and examined for the presence of carbapenemases and integrons. Results. : Almost all A. baumannii isolates were extensively drug‐resistant (XDR; 98%) and carried an OXA carbapenemase gene ( bla OXA‐23 ‐like; 98%) and class 1 integrons (48%). PFGE and MLST analysis identified three major genotypes, all belonging to clonal complex 92 (CC92): sequence type 848 (ST848) ( n =23), ST451 ( n =16) and ST195 ( n =8). CC92 has previously been documented in the hospital setting in northern Iran, and ST195 has been reported in Arab States of the Persian Gulf. These data suggest national and global transmission of A. baumannii CC92. Conclusion. : This report demonstrates the occurrence and potential spread of closely related XDR genotypes of A. baumannii CC92 within a university hospital in southern Iran. These genotypes were found in the majority of the investigated isolates, showed high prevalence of bla OXA‐23 and integron class 1, and were associated with stay in the intensive care unit. Very few treatment options remain for healthcare‐adapted XDR A. baumannii, and hence effective measures are desperately needed to reduce the spread of these strains and resultant infections in the healthcare setting.